Mapping state and non-state actors' responses to nuclear energy in Southeast Asia - Putra, Nur Azha; Anthony, Mely Caballero (World Scientific, 2017)
This book aims to introduce and discuss the policy issues and challenges surrounding the development of nuclear power energy in Southeast Asia (SEA). Nuclear energy is poised for substantial growth in a region that is in need of more sustainable and clean energy source against the background of rising energy demand and an increasingly narrower power supply and demand gap. However, there are many safety and security risks associated with nuclear power especially so for a region that remains vulnerable to political risks and military conflicts. This book will, therefore, discuss those policy issues and challenges and offers unique insights from the practitioners, industry experts, academics, and policymakers on how the SEA governments could mitigate those risks through good governance.